Adolescence - Santrock, John W. (New York, NY : McGraw-Hill, 2012)
'More students learn from John Santrock's Adolescence than from any other text in this field. The 14th edition combines proven pedagogy and the most current research to provide a market leading presentation of adolescence. This time tested text provides compelling contemporary research, including updates from eleven leading experts in the field. The text's accessible presentation, plentiful applications and engaging writing foster increased mastery of the content. The new edition includes substantially expanded material on diversity and culture, adolescents' and emerging adults' health and well-being, including numerous recommendations for improving the lives of adolescents, and expanded emphasis on the positive aspects of adolescent development'--
Machine generated contents note: ContentsChapter 1: Introduction The Historical PerspectiveToday's Adolescents in the United States and Around the WorldThe Nature of Development The Science of Adolescent DevelopmentReach Your Learning GoalsChapter 2: Puberty, Health, and Biological FoundationsPubertyHealthEvolution, Heredity, and EnvironmentReach Your Learning GoalsChapter 3: The Brain and Cognitive DevelopmentThe BrainThe Cognitive Developmental ViewThe Information-Processing ViewThe Psychometric/Intelligence ViewSocial CognitionReach Your Learning GoalsChapter 4: The Self, Identity, Emotion, and PersonalityThe SelfIdentityEmotional DevelopmentPersonality DevelopmentReach Your Learning GoalsChapter 5: GenderBiological, Social, and Cognitive Influences on GenderGender Stereotypes, Similarities, and DifferencesGender-Role ClassificationDevelopmental Changes and JuncturesReach Your Learning GoalsChapter 6: SexualityExploring Adolescent SexualitySexual Attitudes and BehaviorNegative Sexual Outcomes in AdolescenceSexual Literacy and Sex EducationReach Your Learning GoalsChapter 7: Moral Development, Values, and ReligionDomains of Moral DevelopmentContexts of Moral DevelopmentValues, Religions, and CultsReach Your Learning Goals Chapter 8: FamiliesFamily ProcessesAdolescents' and Emerging Adults' Relationships with their ParentsSibling RelationshipsThe Changing Family in a Changing SocietySocial Policy, Adolescents, and FamiliesReach Your Learning GoalsChapter 9: Peers, Romantic Relationships, and Life StylesExploring Peer RelationsAdolescent GroupsGender and CultureDating and Romantic RelationshipsEmerging Adult LifestylesReach Your Learning GoalsChapter 10: SchoolsApproaches to Educating StudentsTransitions in SchoolingThe Social Contexts of SchoolsAdolescents Who Are ExceptionalReach Your Learning GoalsChapter 11: Achievement, Work, and CareersAchievementWorkCareer DevelopmentReach Your Learning GoalsChapter 12: CultureCulture, Adolescence, and Emerging AdulthoodSocioeconomic Status and PovertyEthnicityThe Media and TechnologyReach Your Learning GoalsChapter 13: Problems in Adolescence and Emerging AdulthoodExploring Adolescent and Emerging Adult ProblemsProblems and DisordersInterrelation of Problems and Prevention/InterventionReach Your Learning GoalsAppendix: Careers in Adolescent Development.
Includes bibliographical references and index.
Buku bacaan asas fakulti.
Keywords: Adolescence; Adolescent psychology